THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND THE INCIDENCE OF STUNTING IN TODDLERS - Dita Hasni; Natasya Syifa Anugrah; Zilhadi Al Asri; Sri Nani Jelmila (Yayasan Nusantara Hasana Berdikari, 2023)
Motivation/Background. Stunting represents a prevalent health issue, particularly in lower to middle-income countries, including Indonesia. Occurring predominantly among infants, stunting is influenced by various factors such as genetics and nutritional status, primarily derived from direct dietary intake like breastfeeding. Additionally, socioeconomic factors, including household income, economic status, and food security, also contribute to stunting in young children. The adverse effects of stunting manifest in compromised growth and intellectual development, potentially impeding productivity, elevating the incidence of low birth weight, and increasing the risk of degenerative diseases. These consequences may subsequently heighten the risk of future poverty. This study aims to explore the relationship between exclusive breastfeeding and the incidence of stunting in infants. Method: The research adopts a (narrative/systematic) review methodology, guided by the PRISMA 2020 framework. Data was gathered through searches on Google Scholar and PubMed, focusing on publications from 2019 to 2023. The search keywords included